Probiotics and Acidifiers Enhance Intestinal Mucosal Resistance to APEC in Broilers - Koesnoto Supranianondo; Kartika Purnamasari; Andreas Berny Yulianto (Universitas Airlangga, 2026)
Avian pathogenic Escherichia coli (APEC) causes disease in poultry and results in economic losses through reduced hatchability, production, and increased morbidity and mortality. This study evaluated the potential of probiotics and acidifiers to improve intestinal mucosal resistance in APEC-infected broilers. A completely randomized design was used, including six treatments with five replicates (n=30): T0(–) uninfected control, T0(+) infected control, T1 antibiotic growth promoter (AGP), T2 probiotics (5 mL/L drinking water), T3 acidifiers (5 g/kg feed), and T4 probiotics + acidifiers. The variables measured were intestinal lesions (necrosis, degeneration, and inflammation), villus morphology (height, width, and area) in the duodenum and jejunum, and feed conversion ratio (FCR). Data were analyzed using ANOVA and Duncan’s test, while lesion scores used Kruskal–Wallis and Mann–Whitney tests. All treatments differed from those of the infected control. Probiotics and acidifiers improved villus morphology and produced lower FCR than AGP, whose FCR was similar to that of the infected control. Probiotics and acidifiers show potential as alternatives to AGP in maintaining intestinal integrity in APEC-challenged broilers.